2019
DOI: 10.1016/j.ijcard.2018.10.080
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation for fascicular ventricular tachycardia: A systematic review

Abstract: Introduction: Catheter ablation has been evaluated as treatment for fascicular ventricular tachycardia (FVT) in several single-centre cohort studies, with variable results regarding efficacy and outcomes. Methods: A systematic search was performed on PubMed, EMBASE and Cochrane database (from inception to November 2017) that included studies on FVT catheter ablation. Results: Thirty-eight observational non-controlled case series comprising 953 patients with FVT undergoing catheter ablation were identified. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…Twenty-five patients were male, and eight were female. The mean weight of the patients was 39.6 ± 10.4 kg (22-86), and the mean age was 13.6 ± 2.5 years (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The indication for ablation was decreased left ventricular systolic function, revealed by echocardiography (EF: 45%) in one patient due to incessant fascicular tachycardia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five patients were male, and eight were female. The mean weight of the patients was 39.6 ± 10.4 kg (22-86), and the mean age was 13.6 ± 2.5 years (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The indication for ablation was decreased left ventricular systolic function, revealed by echocardiography (EF: 45%) in one patient due to incessant fascicular tachycardia.…”
Section: Resultsmentioning
confidence: 99%
“…However, compared to adult patients, the success rate was significantly lower in paediatric studies (90% versus 94.3%). 7 Use of a threedimensional electroanatomic mapping system varied significantly among studies included in the review. In our procedures, threedimensional electroanatomic mapping systems helped confirm the exact catheter position prior to ablations, allowing us to label the location of ablation lesions on the three-dimensional map.…”
Section: Discussionmentioning
confidence: 99%
“…IV verapamil is considered the gold standard in the initial emergent management, followed by long-term catheter ablation (CA) [9]. CA is effective in curing almost 90% of the disease in the long term [10]. In patients who are not willing to undergo CA, oral verapamil has been less successful for the permanent cessation of the arrhythmia but is likely the best option for outpatient management [5].…”
Section: Discussionmentioning
confidence: 99%
“…31 By combining results from 8 studies with 65 patients affected by MEPPC syndrome, female sex slightly predominates (60%). In the largest review of 953 patients with fascicular VT undergoing catheter ablation, Creta et al 32 showed that male sex was predominant (82%), which may appear in discrepancy with LV PurkEs predominating in women. However, fascicular VTs are mainly attributable to reentry with conduction disturbance in the Purkinje fascicles and myocardium while ectopic triggers mainly involve triggered activity mechanisms.…”
Section: Sex-related Arrhythmia Manifestationsmentioning
confidence: 99%